Evaluation of Anticoagulant Proteins and Fibrinolytic System Markers in Children with Pneumonia - Zahide Yalaki; Bülent Alioğlu; Nurdan Çiftçi; Fatma İnci Arıkan (Galenos Yayinevi, 2019)
Aim:Coagulation and fibrinolytic systems play an important role in the pathogenesis of complicated pneumonia. This study aims to evaluate and compare coagulation and fibrinolytic system markers and natural anticoagulant proteins with acute phase reactants, such as C-reactive protein or procalcitonin in children with pneumonia.Materials and Methods:One hundred and fifteen patients and 87 healthy children were included in the study. Patients were separated into two groups based on viral and bacterial pneumonia diagnosis. Coagulation and anticoagulation system markers were compared with acute phase reactants in children with pneumonia.Results:White blood cell numbers and D-dimer (DD) levels were higher in the pneumonia patients compared to the control group (p=0.001 and 0.001 respectively). Protein C activity and antithrombin activity in the patient group were significantly lower compared to the control group (p=0.001 and p=0.011 respectively). Acute phase reactants and DD levels in the bacterial pneumonia patients were higher compared to the viral pneumonia patients (p<0.05). Protein S activity, fibrin monomers and fibrin degradation products were not significantly different between the bacterial and viral pneumonia patients. Protein S activity in the bacterial pneumonia patients was lower compared to the viral pneumonia patients (p=0.040). There was no difference in terms of antithrombin activity and protein C activity.Conclusion:As a result, the relationships among acute phase proteins, anticoagulation proteins, and fibrinolytic system markers show that the coagulation and fibrinolytic system has an important role in pneumonia pathogenesis and associated inflammation. Evaluation of the coagulation system may help determine the severity of pneumonia in children and be used to monitor its clinical progress.